Mexican Natural Resources Management and Biodiversity Conservation Recent Case Studies (Springer International Publishing, 2018)
This book presents valuable and recent lessons learned regarding the links between natural resources management, from a Socio-Ecological perspective, and the biodiversity conservation in Mexico. It address the political and social aspects, as well as the biological and ecological factors, involved in natural resources management and their impacts on biodiversity conservation. It is a useful resource for researchers and professionals around the globe, but especially those in Latin American countries, which are grappling with the same Bio-Cultural heritage conservation issues.